Improving vibration test methods and profile selection for complex land vehicle payloads. Issue 1 (1st January 2019) - Warren, Mark; Joiner, Keith F.
ABSTRACT: Mechanical vibration testing is used within the Department of Defence for acceptance testing of land materiel. Historical testing has commonly implemented default vibration profiles listed in defence standards. These profiles have limitations and assumptions which may restrict their suitability for large and complex payloads due to divergences from theoretical models. Research has also highlighted inaccuracies with the Gaussian and stationary assump-tions inherent in Power Spectral Density (PSD) profile-based vibration testing that could be a source of uncertainty when simulating non-stationary environments. Further research is pro- posed to develop a standardised method to convert measured accelerometer data into PSD profiles, or other input data that can be replicated on a shaker table. This paper overviews the proposed research, in particular quantifying the assumptions, inaccuracies and inefficiencies of the extant and proposed test methods. It also offers practical suggestions on how to implement these methods to ensure risks are adequately managed and communicated.